On taking into account the geographical factor when planning the development of the Kuzbass economy - Aleksandr N. Solovitskiy (Наука Красноярья)
It is shown that taking into account the geographical factor in relation to the economy of Kuzbass is characterized by significant limitations. Under the current conditions, the author proposed to develop new scientific and methodological principles for taking into account the geographical factor in the framework of improving the model of territorial planning in Kuzbass, which is an important scientific task. The author proposes a new approach based on new five principles, reflecting not only the acquisition of new applied knowledge for interdisciplinary use, but also bringing the concepts of «territorial planning» and «geographical factor» closer together. The practical use of the research results is to expand the consideration of the geographical factor for the development of the region